2016
DOI: 10.1159/000447097
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in End-of-Life Communication and Preferences among Chronic Kidney Disease Patients

Abstract: Background: Previous studies on end-of-life (EOL) care among patients with chronic kidney disease (CKD) have been largely limited to White hemodialysis patients. In this study, we sought to explore racial variability in EOL communication, care preferences and advance care planning (ACP) among patients with advanced CKD prior to decisions regarding the initiation of dialysis. Methods: We performed a cross-sectional study between 2013 and 2015 of Black and White patients with stage IV or V CKD (per the Modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 40 publications
2
56
0
Order By: Relevance
“…Hispanic race was independently associated with poorer survival after in‐hospital CPR in patients with ESLD, a finding that warrants further investigation. Prior studies have shown that patients of Hispanic origin have a higher likelihood of receiving intensive medical care at end‐of‐life compared to patients from other racial/ethnic groups . These findings have been attributed to various factors, such as cultural and religious beliefs, language barriers, overly optimistic beliefs in the effectiveness of life‐prolonging therapies and reduced rates of code status documentation in this population .…”
Section: Discussionmentioning
confidence: 93%
“…Hispanic race was independently associated with poorer survival after in‐hospital CPR in patients with ESLD, a finding that warrants further investigation. Prior studies have shown that patients of Hispanic origin have a higher likelihood of receiving intensive medical care at end‐of‐life compared to patients from other racial/ethnic groups . These findings have been attributed to various factors, such as cultural and religious beliefs, language barriers, overly optimistic beliefs in the effectiveness of life‐prolonging therapies and reduced rates of code status documentation in this population .…”
Section: Discussionmentioning
confidence: 93%
“…We also found independent relationships between ACP knowledge and other sociodemographic factors, including Spanish language and nonwhite race, similar to other studies. 32,33 Prior studies, however, did not assess health literacy, preferred language, finances, or social support. Reasons for these associations may overlap with reasons why these groups have lower rates of ACP, including differences in access to care and varying levels and acculturation and cultural differences.…”
Section: Discussionmentioning
confidence: 99%
“…9, 33 Patients may feel more inclined to have discussions with their providers whom they feel comfortable with however, relationships with health care providers may have less of an impact on subsequent treatment decision-making among minority racial patients. For instance, Smith et al showed that although the quality of the physician-patient relationship (e.g., perceived respect, listening, help in navigating the medical system) was lower among Black patients compared with White patients, this did not influence advance care planning or preferences for life-sustaining treatments.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, given the higher incidence of limited health literacy among Black patients, there is evidence that health literacy is a mediator of racial disparities across several parts of care. 1013 Limited health literacy impedes an individual’s capacity to understand basic information to make informed medical decisions and approximately 28–32% of patients with CKD are afflicted.…”
mentioning
confidence: 99%